Hubungan antara Kebiasaan Membaca dengan Hasil Belajar Bahasa Indonesia di SD Negeri Tingkir Tengah 02 - Erika Ayu Anggraini (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2018)
The purpose of this study was to determine the relationship between reading habits with Indonesian Language learning results in SD Negeri Tingkir Tengah 02. This type of study using the quantitative-correlational study to see the relation between two variables. There are two variables used in this study is the habit of reading results (X) and Indonesian Language learning(Y). The instruments used in this study is now the habit of reading and learning result of Indonesian Language. The Pearson correlation test result shows the correlation coefficient of 0.010 in the interval coefficient of 0.00 – 0.199 and the significance coefficient 0.949>0.005of alpha coefficients. Then the conclusion of the execution of the study is there is a very weak correlation, positive, and not significant between the habit of reading with Indonesian Language learning result SD Tingkir Tengah 02.